Perceptions on a mobile health intervention to improve maternal child health for Syrian refugees in Turkey: Opportunities and challenges for end-user acceptability - Christina L. Meyer; Aral Surmeli; Caitlyn Hoeflin Hana; Nirmala P. Narla (Frontiers in Public Health, 2022)
BackgroundMobile health (mhealth) technology presents an opportunity to address many unique challenges refugee populations face when accessing healthcare. A robust body of evidence supports the use of mobile phone-based reminder platforms to increase timely and comprehensive access to health services. Yet, there is a dearth of research in their development for displaced populations, as well as refugee perspectives in design processes to improve effective adoptions of mhealth interventions.ObjectiveThis study aimed to explore healthcare barriers faced by Syrian refugee women in Turkey, and their perceptions of a maternal-child health mobile application designed to provide antenatal care and vaccine services. These findings guided development of a framework for enhancing acceptability of mobile health applications specific to refugee end-users.MethodsSyrian refugee women who were pregnant or had at least one child under the age of 2 years old at the time of recruitment (n = 14) participated in semi-structured in-depth interviews. Participants had the opportunity to directly interact with an operational maternal-child health mobile application during the interview. Using a grounded theory approach, we identified critical factors and qualities mhealth developers should consider when developing user-friendly applications for refugees.ResultsIt was observed that a refugee's perception of the mobile health application's usability was heavily influenced by past healthcare experiences and the contextual challenges they face while accessing healthcare. The in-depth interviews with refugee end-users identified that data security, offline capability, clear-user directions, and data retrievability were critical qualities to build into mobile health applications. Among the features included in the maternal-child health application, participants most valued the childhood vaccination reminder and health information features. Furthermore, the application's multi-lingual modes (Arabic, Turkish, and English) strengthened the application's usability among Syrian refugee populations living in Turkey.ConclusionsThe inclusion of refugee perceptions in mhealth applications offers unique developer insights for building more inclusive and effective tools for vulnerable populations. Basic upfront discussions of the mobile application's health goals and its personal value to the user may improve their long-term use. Further prospective research is needed on retention and use of mobile health applications for refugee women and other displaced populations.